Proximate, Phytochemical Analisys and Phenol Content of Javanese Long Pepper (Piper retrofractum Vahl) from Several Regions in Madura: Analisis Proksimat, Fitokimia dan Kadar Fenol Cabe Jamu (Piper retrofractum Vahl) dari Beberapa Daerah di Madura - Nurhidayah, Enung; Hidayati, Darimiyya; Habiba , Risqina Amily; Maulidya, Syafira (Universitas Slamet Riyadi Surakarta, 2024)
Javanese long pepper (Piper retrofractum Vahl) is a native Indonesian spice that is found in many regions in Indonesia, especially in Madura. The cultivation of Javanese long pepper plants is spread across four large areas in Madura, that are Sumenep, Pamekasan, Sampang, and Bangkalan. Empirically, herbal chilies have been proven to be able to treat various diseases. This is closely related to the macronutrient content and bioactive compounds contained in herbal chilies. This research has carried out proximate analysis, phytochemical screening and phenolic content analysis of herbal chilies originating from four regions in Madura. The analysis results showed that Sumenep herbal medicine chili extract had the highest number of calories at 8,434 kcal. Meanwhile, Bangkalan herbal medicine chili extract has the lowest number of calories, namely 8,227 kcal. The results of this research also showed that Javanese long pepper contain six active compounds, five of which have been successfully tested with positive results (+) or have been proven to contain alkaloids, terpenoids, tannins, flavonoids, and carotenoids. Saponin compounds showed negative results (-) or there were no saponin compounds in Madurese herbal chilies. The total phenolic content of local Madurese herbal chilies from Pamekasan, Sampang, Sumenep and Bangkalan respectively, 44.63; 27.70; 25.49; and 22.70 mg GAE/g. The results showed that there were significant differences between the areas of the Javanese long pepper in terms of water content, protein content, fat content, carbohydrate content and phenol content (p<0.05).